AN ANALYSIS OF THE PORTUGUESE VENTURE CAPITAL MARKET: PARTIAL EXITS VERSUS TOTAL EXITS - Félix, Elisabete Gomes Santana (2012)
This article analyzes Portuguese venture capital exits, exploring the relationship between the type of exit and the asymmetry of information of the venture capital investments. The central hypothesis being tested is that the occurrence of partial exits is associated with signalling the investment quality and with the reduction of the degree of informational asymmetry. The data resulted from a study elaborated by Small Business Investment, SA and Price WaterHouse Coopers, for the Associação Portuguesa de Capital de Risco e de Desenvolvimento (APCRI), by way of questionnaire sent to the resident Portuguese venture capital companies. We used Logit models in which the dependent variable is a dummy indicating if a partial exit occurred and the independent variables are all dummies referring to investment and divestment characteristics. We conclude that when the exit occurs through IPO, this increases the probability of a partial exit occurring and that the longer the duration, the smaller is the probability of a partial exit. Both results support the hypothesis that the higher the degree of informational asymmetry, the higher the probability of a partial exit.